Search Optimization of a Web Site Based on the Content Analysis - O. Romeyko; S. Mikhnevich (Цифровая трансформация)
The paper presents the algorithm of "white" optimization of the website and its implementation. The algorithm solves the problem of optimization of web applications, without special services of specialists. On the basis of this algorithm it is realized the system, which provides recommendations for optimization of the web application in automated mode.